Fouling of a boat hull by the invasive zooxanthellate coral Oculina patagonica - could shipping be enhancing its unique large-scale spread? - SERRANO, EDUARD; RIBES, MARTA; BOLIVAR, MANEL; COMA, RAFAEL (Mediterranean Marine Science, 2023)
The zooxanthellate coral Oculina patagonica (Scleractinia, Oculinidae) is an invasive species that was first recorded in the Mediterranean Sea in 1966 and currently has expanded its distribution across both the western and eastern Atlantic. Here, we reviewed data from multiple databases to compile historical distribution records of O. patagonica and analyze its spread. The chronological review highlights the unique spread of this zooxanthellate coral during the last two decades, expanding its distribution in multiple directions and establishing populations in disjunct regions separated by 12,000 km, including most biogeographic regions within the temperate Mediterranean, the subtropical eastern Atlantic and the tropical Gulf of Mexico. The biogeographic distribution discontinuities documented in O. patagonica are difficult to explain by larval dispersion alone; therefore, other mechanisms may contribute to its large-scale spread pattern. This study provides the first observation of several O. patagonica colonies fouling the hull and metal crevices of a recreational boat in the western Mediterranean (37°N, 1°W). The presence of several mature O. patagonica colonies on a single ship, rather than a single coral colony rafting on natural or artificial floating substrates, could greatly increase its potential for spread, coupled with its ecological and biological traits adapted to rafting. We hypothesized that the travel of coral populations by shipping may act as a dispersal vector contributing to explaining the long-distance dispersal events and secondary introductions experienced by this invasive species. The broad spread of O. patagonica, which is able to drive phase shifts from macroalgae dominance to coral dominance, is consistent with the ongoing process of coral-mediated tropicalization of high-latitude shallow rocky reefs under current global change